Physicochemical properties of three starches derived from potato, chestnut, and yam as affected by freeze‐thaw treatment. Issue 3 (17th October 2013) - Zhang, Wenjing; Chen, Haixia; Wang, Jia; Wang, Yanwei; Xing, Lisha; Zhang, Hua
<x xml:space="preserve">Abstract</x> Starches derived from chestnut, potato, and yam were compared by freeze‐thaw treatments (FTT) from 1 to 5 cycles under the conditions of −18°C for 24 h and then 30°C for 2 h. The microstructure, crystallinity, thermal properties, and physicochemical characteristics were investigated using SEM, XRD, and DSC. Significant differences were found after the FTT for the three kinds of starches. Honeycomb‐like network structures formed after the first FTT cycle and the structures were broken after the fifth freeze‐thaw cycle. The freeze‐thawed chestnut and yam starches showed typical B‐type crystal structures, which were significantly different from native ones (A‐type and C‐type patterns for chestnut and yam starches, respectively). The thermodynamic parameter values (T0, Tp, Tc, and ΔH) of the freeze‐thawed starches increased with the increase of FTT cycles. Among the three types of starch, yam starch showed the higher freeze‐thaw stability than potato and yam starches. The potato starch had the highest RS content, which makes it a good resource for RS production.